One session of 20 ​N cyclic compression induces chronic knee osteoarthritis in rats: A long-term study - Zixi Zhao; Akira Ito; Akihiro Nakahata; Xiang Ji; Chia Tai; Motoo Saito; Kohei Nishitani; Tomoki Aoyama; Hiroshi Kuroki (Osteoarthritis and Cartilage Open, 2022)
Objective: Mechanical stimulation is a risk factor for knee osteoarthritis. Non-surgical compression has been used to study the effects of mechanical stimulation in vivo. However, the long-term effects of low-force compression on knee joint had not been studied. Therefore, we sought to identify the long-term effects of low-force cyclic compression on the rat knee joint. Design: In this study, we applied one session cyclic compression with a peak load of 20 ​N for 60 cycles to the rat knee joint in an approximately 140-degree flexion position (Wistar, male, 12 weeks old), followed by 1 year of observation (including data from 1 week, 2 weeks, 4 weeks, 8 weeks, 6 months, and 1 year after compression), and then performed a sub-regional analysis with hematoxylin-eosin, Safranin O and Fast Green, and MMP13 immunohistochemical staining. Results: We observed osteoarthritis-like cartilage damage, synovial inflammation, and high expression of MMP13 within 1 year after compression. However, these changes progressed slowly, with obvious matrix cracks that did not appear until 1 year after compression. In the regional analysis, we found that low-force compression caused a much slower development of injury at the compression contact site, and no significant structural cartilage damage was observed after 1 year of compression. In contrast, the non-contact site during compression at tibial cartilage in the same joint was the first to show significant structural damage. Conclusion: This study demonstrates that one session of 20 ​N cyclic compression induces a chronic osteoarthritis-like phenotype in the rat knee in the long term.